An adaptive, active noise reduction system in closed space - CIESIELKA, W.; GOŁAŚ, A. (Archives of Acoustics, 2006)
In this article, an active noise reduction system has been described. The ANR system was made on the basis of an finite impulse response filter and realised by LMS or NLMS algorithms. Those algorithms were implemented on the dSPACE card with a floating-point processor TMS320C31. The researches were performed in an enclosure of dimensions 4.4, 3.05, 3.2m. White noise filtered by third and octave filters with mid-band frequency 125Hz were used for the experiments. The result of experiments was a reduction of the sound pressure level, meanly from 10 to 20dB for the natural sound field. The investigations performed revealed that the location of reference and error microphones in the acoustic system - in the room, influence significantly the efficiency of the ANR system working. The investigations performed in a selected room (volume V=41.6m3 and reverberation time T=0.53s) revealed that projected and built up system gives very good effects in the active noise reduction for random, white noises of selected ranges.